Nickel‐Catalyzed Intermolecular Branched/Linear Regioselective C−H Alkylation of 4‐Oxoquinazolines. Issue 4 (31st January 2023) - Zhang, Yaqi; Qin, Shengxiang; Pan, Bendu; Cao, Rihui; Sun, Raymond Wai‐Yin; Qiu, Liqin
Abstract: A Ni−NHC‐catalyzed prototype reaction based on the alkylation of C−H activated 4‐oxoquinazolines with aryl and alkyl alkenes was demonstrated. When aryl alkenes are used as the substrates, the regioselection of the reaction can be fine‐tuned by choosing a NHC ligand with appropriate steric hindrance to harvest branched adducts, while the use of a bulky NHC/alkyl aluminum cocatalyst system helps to steer the reaction towards linear products. For alkyl alkene substrates, Ni(cod)2, IMes ⋅ HCl and NaO t Bu system can directionally generate linear products, and long‐chain olefins are also applicable. In addition, the catalytic mechanism was also explored through the deuteration experiments, and the migration of nickel was suggested in the catalytic cycle. Abstract :